Efektivitas Layanan Informasi Terhadap Bahaya Merokok Bagi Siswa di MAS Al-Washliyah P. Brandan Langkat - N, Nuraida; Syukri, Makmur; Hasibuan, Ali Daud (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to know the effectiveness of information services on students’ understanding regarding the harms of smoking in MAS Al-Washliyah P. Brandan Langkat on how important knowledge about the harms of smoking is. In addition to improving students’ knowledge and awareness of the dangers of smoking, supporting better decisions and increasing the efficiency and productivity of the students. Information services can help improve quality of life and support education. Smoking is a common activity engaged in by students especially male adolescents. This can impact on various aspects of his/her life such as health, financial, social, psychological and environmental. The study aims to provide students with an understanding of the dangers of smoking. The research methodology employed a quantitative approach. The population of the study was students of MAS Al-Washliyah P. Brandan Langkat with a total sample size of 36 students. Sampling technique was conducted using random sampling technique established by the researcher. Data collection techniques by means of documentation, interviews and questionnaires. The data analysis/hypothesis testing tool uses the pre-experimental design (impure experiment) formula on SPSS processing. The results of the research conducted by the researcher obtained that the insight of the harms of smoking can be improved through increasing students’ knowledge of the harms of smoking by providing them with appropriate information services so this study shows Ho rejected and Ha accepted with a sig value of 0.000  0.05 given the effect of informational harmfulness in which the study permeates harmfulness. MAS Al-Washliyah P. Brandan Langkat can be remembered.